Penyuluhan Interaktif Tentang Pubertas dan Kesehatan Reproduksi Remaja bagi Siswa SMP Negeri 14 Jember - Eryani, Mikhania Christiningtyas; Winarti, Lina; Wardhani, Firdha Aprilia (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2024)
This community service activity aims to increase the knowledge of students of SMP Negeri 14 Jember regarding puberty and reproductive health in order to realize healthy adolescents for Indonesia Emas 2045. The method used in this activity is the interactive counseling method. The evaluation instrument for this community service is a questionnaire and is analyzed descriptively qualitatively and quantitatively. The results of the community service show that there is an increase in student knowledge which initially had a score of 41.4 before the counseling to 84.1 after the counseling. So that the increase in participant scores after the community service process was carried out was 42.7 or 103%. Through this community service activity, adolescents at SMP Negeri 14 Jember increased their knowledge, especially regarding puberty and reproductive health.